2010
DOI: 10.1007/s11628-010-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Web 2.0 service adoption and entrepreneurial orientation

Abstract: The purpose of this study is to investigate the relationship between Web 2.0 service adoption and entrepreneurial orientation (EO). For this purpose, this article conducted multivariate analysis of variance (MANOVA) using Web 2.0 service adoption groups (high and low adopters) as an independent variable and EO as dependent variable, measured with four variables: innovativeness, risk taking, autonomy, and competitive aggressiveness. The results show that there are significant differences in EO, overall and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…In addition to this, the Web 2.0 constitutes an Internet-based digital platform that enables the creation of social networks, facilitating information dissemination and knowledge sharing (Joo and Normatov 2013;Pan 2012). Consequently, firms are deploying Web 2.0 technologies such as social networking, wikis, and internal blogging to improve collaboration and knowledge sharing within their boundaries (Lim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the Web 2.0 constitutes an Internet-based digital platform that enables the creation of social networks, facilitating information dissemination and knowledge sharing (Joo and Normatov 2013;Pan 2012). Consequently, firms are deploying Web 2.0 technologies such as social networking, wikis, and internal blogging to improve collaboration and knowledge sharing within their boundaries (Lim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Patrick and Dotsika (2007) Finally, a recent study found that Web 2.0 adoption is positively related to entrepreneurial orientation, where high Web 2.0 adopters showed higher mean values of innovativeness, a dimension of entrepreneurial orientation (Lim et al, 2010).…”
Section: Web 20 Mo and Innovativenessmentioning
confidence: 99%
“…Some authors mention that organizations are using Web 2.0 technologies to improve decision cycle times, organizational effectiveness and innovation (Lim et al, 2010). In this article we want to empirically analyze if the adoption of these technologies is related to market orientation and to innovativeness.…”
Section: Introductionmentioning
confidence: 99%
“…The Web 2.0 constitutes an Internet-based digital platform that enables the creation of social networks, facilitating information dissemination and knowledge sharing (Joo & Normatov, 2013). Consequently, fi rms are deploying Web 2.0 technologies, such as social networking, wikis, and blogging to improve collaboration and Web 2.0 knowledge sharing within their boundaries (Lim, Trimi & Lee, 2010). In addition, although the literature suggests that the fi ndings of studies examining KM practices in large companies are unlikely to be generalizable to SMEs, very few and recent studies focus on this specifi c type of fi rms (Chan, Chong & Zhou, 2012;Huy, Rowe, Truex & Huynh, 2012).…”
Section: Introductionmentioning
confidence: 99%